Prevalence and genotype–phenotype correlations of GBA‐related Parkinson disease in a large Chinese cohort. (9th January 2022) - Ren, Jingru; Zhang, Ronggui; Pan, Chenxi; Xu, Jianxia; Sun, Haochen; Hua, Ping; Zhang, Li; Zhang, Wenbin; Xu, Pingyi; Ma, Changyan; Liu, Weiguo
Abstract: Background and purpose: Variants in the glucocerebrosidase ( GBA ) gene are recognized as a common and important genetic risk factor for Parkinson disease (PD). However, the impact of variant severity on the clinical phenotype of PD in the Chinese population remains unclear. Thus, the present study aimed to determine the frequency of GBA ‐related PD ( GBA ‐PD) and the relationship of GBA variant severity with clinical characteristics in a large Chinese cohort. Methods: Long‐range polymerase chain reaction and next generation sequencing were performed for the entire GBA gene. GBA variant severity was classified into five classes: mild, severe, risk, complex, and unknown. Results: Among the total 737 PD patients, 47  GBA variants were detected in 79 (10.72%) patients, and the most common GBA variants were R163Q, L444P, and R120W. Complete demographic and clinical data were obtained for 673 patients, which revealed that 18.50% of early onset PD patients had GBA variants. Compared with patients without GBA variants, GBA ‐PD patients experienced PD onset an average of 4 years earlier and had more severe motor and nonmotor symptoms. Patients carrying severe and complex variants had a higher burden of nonmotor symptoms, especially depression, and more mood/cognitive and gastrointestinal symptoms than patients carrying mild variants. Conclusions: GBA ‐PD is highly prevalent in the Chinese population. The severity of GBA variants underlies distinct phenotypic spectrums, with PD patients carrying severe and complex variants seeming to have similar phenotypes. PD patient stratification by GBA variant severity should become a prerequisite for selecting specific treatments. Abstract : The severity of GBA variants underlies distinct phenotypic spectrums, with Parkinson disease (PD) patients carrying severe and complex variants seeming to have similar phenotypes. PD patient stratification by GBA variant severity should become a prerequisite for selecting specific treatments.